In vitro anti - candida activity of an indigenous mouth wash used in Ayurveda practice: Nadesakanthan S.1, Sanjeewa A.1, Uluwaduge D.I.2, Peiris K.P.P.3* and Meedin F.1 (Sri Lanka Journal of Indigenous Medicine (SLJIM), 2024)
The relation between oral diseases and the activities of microbial species that form part of the micro biota of the oral cavity is well established. This study was focused to investigate anti-candida effect of an indigenous mouth wash used in Ayurveda practice which is mentioned in authentic text as Gandusha (mouth wash). Candida albicans is the most common fungal pathogen effects on oral mucosa. The study was based on anti-candida susceptibility test by using clinically isolated culture of Candida albicans as “standard fungal pathogen”, sterile normal saline as a “negative control” and antifungal solution as “positive control” using agar well diffusion method having 8mm diameter wells. Each well was loaded with 75µl of aqueous extract of an indigenous mouth wash and Amphotericin B anti-fungal preparation as positive control against Candida albicans. 75µl of sterile distilled water was pipetted into the remaining well as negative control. Each sample was triplicated. The results revealed that the indigenous mouth wash inhibited the clinical isolates of Candida albicans (zone of inhibition=10±0.22 mm) and has considerable anti-candida activity against clinically isolated Candida albicans.